Toward a Biopsychosocial Welfare State? How Medicine and Psychology Transform Social Policy - Reibling, Nadine; Ariaans, Mareike (Springer Nature, 2023)
This open access book analyses the idea that medicine and psychology have a substantial (and underestimated) impact on Western welfare states. Based on mixed-methods analyses conducted in Germany, it analyses this influence on debates and policies related to unemployment, poverty, and childhood. The book demonstrates how the turn to neoliberalism and social investment thinking has created this medicalisation and psychologisation of social policies, and the contributions provide important insights for students and scholars of sociology of health and illness, political sociology, social and health policy, medicine, psychology, and public health.